2011
DOI: 10.1186/1472-6882-11-86
|View full text |Cite
|
Sign up to set email alerts
|

Tannin extracts from immature fruits of Terminalia chebula Fructus Retz. promote cutaneous wound healing in rats

Abstract: BackgroundTannins extracted from immature fruits of Terminalia chebula Fructus Retz. are considered as effective components promoting the process of wound healing. The objective of this study is to explore the optimal extraction and purification technology (OEPT) of tannins, while studying the use of this drug in the treatment of a cutaneous wound of rat as well as its antibacterial effects.MethodsThe content of tannin extracts was measured by the casein method, and antibacterial ability was studied by the mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(82 citation statements)
references
References 26 publications
1
76
0
5
Order By: Relevance
“…Of these, perhaps the best documented and the most extensively studied are the Asian Terminalia species used in Ayurvedic medicine. T. arjuna (Chaudhari and Mengi 2006), T. chebula (Li et al 2011;Suguna et al 2002) and T. coriacea (Ali Khan et al 2012) have all demonstrated an ability to hasten the wound healing process. As wound healing is a complex process involving several bioactivities, no single experimental model is adequate to evaluate wound healing and various individual bioactivities need to be considered.…”
Section: Wound Healingmentioning
confidence: 96%
See 2 more Smart Citations
“…Of these, perhaps the best documented and the most extensively studied are the Asian Terminalia species used in Ayurvedic medicine. T. arjuna (Chaudhari and Mengi 2006), T. chebula (Li et al 2011;Suguna et al 2002) and T. coriacea (Ali Khan et al 2012) have all demonstrated an ability to hasten the wound healing process. As wound healing is a complex process involving several bioactivities, no single experimental model is adequate to evaluate wound healing and various individual bioactivities need to be considered.…”
Section: Wound Healingmentioning
confidence: 96%
“…Transcription factors are active in their reduced form and their translocation to the nucleus is also redox dependent (Okamato et al 1999). Studies have demonstrated that T. chebula treatment increases transcription and translation rates as well as DNA replication (Li et al 2011;Suguna et al 2002). These studies also linked these increases to the very high antioxidant activity of T. chebula.…”
Section: Wound Healingmentioning
confidence: 97%
See 1 more Smart Citation
“…Topical administration of an alcoholic extract of T. chebula leaves on the healing of rat dermal wounds showed that T. chebula treated wounds healed faster as indicated by improved rates of contraction and decreased period of epithelialization [85] .…”
Section: Wound Healing Activitymentioning
confidence: 99%
“…Tannins have antioxidant effect and may act in similar fashion to promote collagen deposition [37]. They also increase angiogenesis by increasing vascular endothelial growth factor formation, thus maintaining adequate supply of oxygen necessary for collagen stability [38].…”
Section: Discussionmentioning
confidence: 99%